ECB strategy review - The new pillars: Communication and climate change - Markus Demary; Michael Hüther (Institut der deutschen Wirtschaft (IW), 2020)
The European Central Bank (ECB) is reviewing its strategy. Key pillars are its communication and how monetary policy should address climate change. We advise the ECB to strengthen its communication especially with social groups unfamiliar with monetary policy. When it comes to climate change, the ECB should be responsive, but not activist.
Keywords: 330